An interactive educational blog for Arabic language learners - Awang Ali, Mohammad Amnan (2021)
This project presents an educational blog for learning “Science of al-Bayan” that was specifically designed for Arabic language learners at the Department of Arabic Language and Literature of International Islamic University Malaysia (IIUM). A special prototype courseware in learning ‘Science of al-Bayan’ was designed by using an educational blog, based on ADDIE instructional design model in the design and development process. This educational blog has been used by the students in their learning activities. The educational blog was designed based on students’ needs, opinions and suggestions, which was evaluated by the participants involved in this study, selected among Arabic language learners at the Department of Arabic Language and Literature of International Islamic University Malaysia (IIUM) .